Candida auris colonization or infection of the ear: A single-center study in South Korea from 2016 to 2018. (15th March 2019) - Jung, Jiwon; Kim, Min Jae; Kim, Ja Young; Lee, Jeong-Young; Kwak, Sun Hee; Hong, Min Jee; Chong, Yong Pil; Lee, Sang-Oh; Choi, Sang-Ho; Kim, Yang Soo; Woo, Jun Hee; Kang, Woo Seok; et al.
Abstract: Candida auris was first identified in Japan from specimens obtained from the ear, but most reports since have reported invasive infections or non-ear based cases. We reviewed all the microbiology records from a single center in South Korea from February 2016 to July 2018. One hundred eleven isolates were positive for C. auris from 79 patients. All 79 patients positive for C. auris had positive ear discharge samples. All but one of the patients with C. auris had been to the otorhinolaryngology clinic. Symptom-driven ear culture was done for all but one patient, whose culture was performed for surveillance. Ear discharges were mostly purulent (60%) or serous (34%). We performed the environmental cultures at the otorhinolaryngology outpatient clinic to evaluate the environmental contamination of C. auris, but C. auris was not isolated from medical equipment and environmental surfaces.